No Way Out: Crime, Punishment and the Limits to Power (Transcript and Video) - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2012)
The United States is often hailed as the world's largest 'free market'. But this 'free market' is also the world's largest penal colony. It holds over seven million adults – roughly five per cent of the labour force – in jail, in prison, on parole and on probation. Is this an anomaly, or does the 'free market' require massive state punishment? Why did the correctional population start to rise in the 1980s, together with the onset of neoliberalism? How is this increase related to the upward redistribution of income and the capitalization of power? Can soaring incarceration sustain the unprecedented power of dominant capital, or is there a reversal in the offing?
Keywords: 330; capital as power; crime; Georg Rusche; punishment; systemic crisis; unemployment; United States